Automated Customer Query Resolver Using Data Mining - Wadekar, PH; Wani, BK; Joshi, NN; Jadhav, AW (International Journal of Computer Sciences and Engineering, 2025)
In an enterprise service centre, the biggest problem is to provide accurate information to customers and solve their queries. In this case ,financial as well as human resources are consumed to a greater extent. In order to reduce this problem, there should be an efficient solution. There are some existing technologies which are used by modern enterprise centres. In an enterprise service centre, when the customer places his query, the frequently asked questions are displayed first. If the customer is not satisfied with the solution or if the required content is not available, then the call will be transferred to the enterprise service centre. As the call is placed, the human interaction between the customer and the enterprise service centre will be substantially increased. In this paper, we propose a system which reduces human interaction and provides automation for resolving queries. For this purpose we use the concept of enterprise mobility. Mobility provides exciting opportunities to interact with your customers, partners and suppliers, empower your employees and connect things to your business.